Cordocentesis: indications, usefulness and risks - Noia, G.; Masini, L.; De Santis, M.; Di Lieto, M. P.; Trivellini, C.; Bianchi, A.; Caruso, A.; Mancuso, S. (Medicina e Morale, 1991)
Cordocentesis (sampling of fetal blood from the umbilical cord) is a well known technique in obstetric practice for prenatal diagnosis and therapy. In expert hands this approach is easily applicable and it has a high rate of success; as an invasive procedure it presents low risks to the fetus and mother. Besides, ethical evaluations render it more appropriate for future intrauterine therapy, particularly in the field of genetic diseases.